Posterior Fossa Intra-Axial Lesion: There Are Pathologies Beyond Metastases - Fotakopoulos, George; Brotis, Alexandros G.; Paterakis, Konstantinos; Kapsalaki, Eftychia; Fountas, Kostas N. (Asian Journal of Neurosurgery, 2022)
Cerebellar metastases represent the most common lesion requiring surgical treatment in the daily neurosurgical praxis. We report a rare case with Lhermitte–Duclos disease presenting to the neurosurgical outpatient department and describe our diagnostic and treatment challenges. A 57-year-old man presented with transient cerebellar manifestations, including walking difficulties, dizziness, and a persistent occipital headache. The magnetic resonance imaging demonstrated a high-intensity lesion in the right cerebellar hemisphere on T2-weighted images. We initially considered surgery to establish a histopathological diagnosis. However, the magnetic resonance spectroscopy was compatible with a dysplastic gangliocytoma of the cerebellum. Therefore, we preferred a more conservative approach. Posterior fossa contrast-enhancing lesions are much more than metastases. The role of advanced magnetic resonance in avoiding unnecessary surgical interventions is priceless.
Keywords: Lhermitte–Duclos disease; dysplastic ganglioglioma of the cerebellum; magnetic resonance spectroscopy; asymptomatic cases; cerebellum